Mass segregation in two young clusters in the Large Magellanic Cloud: SL 666 and NGC 2098 - Kontizas, M.; Hatzidimitriou, D.; Bellas-Velidis, I.; Gouliermis, D.; Kontizas, E.; Cannon, R. D. (1998)
The age and dynamics of the young LMC clusters SL 666 and NGC 2098 were investigated using CCD observations obtained with the 3.9m Anglo-Australian Telescope. SL 666 was found to have an age of 1 - 1.25 x 10(8) yr, while NGC 2098 is somewhat younger, with an age of 6.3 - 7.9*E(7) yr. In the case of SL 666 the good quality of the acquired data allowed the construction of the main sequence luminosity function as a function of radius, which revealed mass segregation, also confirmed from star counts. Since the age of SL 666 is significantly lower than the mean relaxation time of at least 5 x 10(8) yr calculated for this cluster and since the mass range of the cluster members does not permit us to assume faster energy equipartition, the observed mass segregation seems to be due to the way stars form in the cluster. Indications on a star formation scenario are examined. Disruption time is also discussed and there is strong evidence that the cluster is bound. NGC 2098 shows strong evidence of mass segregation, but further observations are needed in this case.
Keywords: GALAXIES: MAGELLANIC CLOUDS; galaxies: star clusters; MASS FUNCTION; STARS: HERTZSPRUNG-RUSSEL (HR) DIAGRAM; STARS: LUMINOSITY FUNCTION